2009
DOI: 10.4081/ijas.2009.s2.661
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal responsiveness to a low-dose ACTH challenge in early and late lactating dairy cows

Abstract: To improve the evaluation of the chronic stress conditions, the adrenal responsiveness to low dose ACTH stimulation, in different lactation stages, was checked in 56 multiparous dairy cows from 2 herds (25-350 days in milk). Cows were retrospectively ranked in 3 stages: early (<75) average (75-150) and late (>150 DIM) lactation. Herd B (vs. herd A) showed higher basal cortisol and frequency of inflammation. Early stage (vs. others) showed higher basal cortisol, bilirubin, ceruloplasmin and haptoglobin, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Others have demonstrated no difference in basal plasma glucocorticoids after parturition and in early lactation compared with the nonlactating and pregnant dairy cow (Kejela et al, 1978) or throughout the stages of lactation and pregnancy (Shayanfar et al, 1975). Conversely, Trevisi et al (2009) demonstrated a greater basal cortisol concentrations in early compared with mid-and late-lactation cows, whereas the rise of cortisol in response to ACTH was greater in mid and late lactation. Our results are consistent with the adrenal cortex being more responsive during midlactation compared with the dry period, with no change in sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated no difference in basal plasma glucocorticoids after parturition and in early lactation compared with the nonlactating and pregnant dairy cow (Kejela et al, 1978) or throughout the stages of lactation and pregnancy (Shayanfar et al, 1975). Conversely, Trevisi et al (2009) demonstrated a greater basal cortisol concentrations in early compared with mid-and late-lactation cows, whereas the rise of cortisol in response to ACTH was greater in mid and late lactation. Our results are consistent with the adrenal cortex being more responsive during midlactation compared with the dry period, with no change in sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Most articles on dairy ruminants study the association of plasma cortisol levels with different factors that cause stress in animals, including climatic conditions (Olsson and Dahlborn, 1989;Gudev et al, 2005), management techniques, such as type of food (Marsico et al, 2009), type of housing (Olmos et al, 2009), transport (Canaes et al, 2009), mechanical milking (NegrĂŁo et al, 2004), and offspring suckling (NegrĂŁo, 2008), and animal-related factors such as mammary gland health status (Fox et al, 1981;Hockett et al, 2000;Decarvalho et al, 2009), lactation stage (Trevisi et al, 2009), breed (NegrĂŁo, 2008), parity number (Van Reenen et al, 2002), and milk yield (Sevi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This discomfort among the cows was indicated by the fact that the cows were dirtier, particularly in the udder area, because they lay down in the pasture, which was confirmed by the higher SCC in the same group of cows. Consistent with this claim, DĂ­az et al [ 50 ] listed various factors that can alter plasma cortisol levels, including but not limited to the management system, such as the type of housing [ 54 ] and transport [ 55 ], lactation stage [ 56 ], and milk yield [ 57 ]. Another factor could be the lower feed intake in the 24 hG group compared with the 12 hG group, which can be considered a source of stress, as stated by Gellrich et al [ 51 ] and Fisher et al [ 52 ].…”
Section: Discussionmentioning
confidence: 99%